Discursive-Pragmatic Creativity in English-Language Chinese Mass Media - O. V. Nikolaeva (Научный диалог)
The issue of linguistic creativity in Chinese mass media sources published in English is considered. The novelty of the study lies in the fact that the English-language discourse of the Chinese mass media is studied as an independent culturally conditioned speech activity phenomenon that actualizes the cultural values of China and the civilizational values of the East. It is substantiated that linguistic creativity is realized in English texts through various forms of manifestation of Chinese national communicative identity: proverbs, allegories, analogies, hints, allusions, rooted in Chinese history, philosophy and folk experience. The updated concepts of proverbs emphasize the values of constant evolutionary movement on the principle of “movement in the still” and the values of collectivism, which are significant both in the country itself and in the region and the world. The collectivism peculiar to China determined the accentuation of the anti-value concepts of hegemony, shame, slander and humiliation. It has been proved that linguistic creativity in the Chinese media in English is also expressed in wordplay and word creation, if this contributes to a more effective presentation of China's position to the English-speaking audience and does not violate the principle of appropriateness. It has been established that in the Chinese English-language mass media, linguistic creativity is of a discursive-pragmatic nature, allows copying samples of linguistic creativity from English-language media and is supplemented with new associations and meanings in their own cultural context.